Progression of post-traumatic liver sequestration - Torterolo, Edgardo; Piacenza, Guillermo; Bueno, Marisa; Bergalli, Luis; Goller, Wolfgang; Traibel, Jorge; Cardeza, Héctor; de Vecchi, Jorge; Perrier, José P (Cirugía del Uruguay, 1975)
In 16 hepatic sequestra following mechanical injury, the authors discuss the anatomo-clinical evolution ?f 7. !'he evolutive character of the anatomic lesion is studied, as well as its topography, which was always sectorial or segmentary, thus lendin: support to the hypothesis of the vascular origin of the sequestrum, due to lesion of the afferent and/or efferent vessels of an area of the parenchyma. The means of reducing its morbi-mortality must be searched through a m>re radical approach, seeking for a · clinical and para-clínica! confirmation -arteriography, scintigraphy- of the vascular lesion and removing not only the area devitalized by the injury, but also the whole .rea in which the blood supply was demaged.